The Influence of Emotional Regulation on Academic Resilience in Students Who Are Working on Their Thesis - Budi Prasetyo, Fauzi; Nur’Aini, Aulia; Sarah Febriani, Anggia (International Journal of Social Science, Education, Communication and Economics, 2024)
This study aims to determine the role of emotion regulation on academic resilience in 10th, 12th, and 14th semester students who are working on an undergraduate thesis. The research method used is quantitative, employing multiple regression analysis techniques to analyze the data. The instruments used in this study include the Emotion Regulation Questionnaire (ERQ) scale, developed by Gross and John (2003), to measure emotion regulation, and The Academic Resilience Scale (ARS-30), developed by Cassidy (2016), to measure academic resilience. The results of the study reveal that there is a significant positive effect of cognitive reappraisal emotion regulation on academic resilience among students in their 10th, 12th, and 14th semesters who are working on their thesis, accounting for 27.1% of the variance in academic resilience. This finding suggests that students who engage in cognitive reappraisal, a strategy that involves reinterpreting a situation to change its emotional impact, are more likely to demonstrate resilience in the face of academic challenges. In contrast, the study found no significant effect of expressive suppression emotion regulation on academic resilience in the same group of students. Expressive suppression, which involves inhibiting the outward expression of emotions, does not appear to contribute to the ability of students to remain resilient while working on their thesis. These findings highlight the importance of cognitive emotion regulation strategies in fostering academic resilience among students, particularly during challenging academic tasks such as thesis completion.